2012
DOI: 10.1074/jbc.m112.375964
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl Hydroxylase 3 (PHD3) Modulates Catabolic Effects of Tumor Necrosis Factor-α (TNF-α) on Cells of the Nucleus Pulposus through Co-activation of Nuclear Factor κB (NF-κB)/p65 Signaling

Abstract: Background:The regulation of PHD expression and function under inflammatory conditions in the nucleus pulposus is unknown. Results: Expression of PHD3 is regulated by TNF-␣ and IL-1␤. PHD3 controls TNF-␣ activity by modulating NF-B signaling. Conclusion: PHD3 promotes the catabolic effects of TNF-␣ on nucleus pulposus cells. Significance: PHD3 may play an important role in pathogenesis of disc disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 30 publications
6
66
1
Order By: Relevance
“…Previous studies by our group and others have implicated several IL-1␤-induced genes in the progression of intervertebral disc degeneration, including matrix degrading enzymes, MMP-3, and ADAMTS-5, as well as PHD3 and syndecan 4 (3,34,35). Although CCN2 treatment alone had little effect on basal expression of these catabolic genes, when combined with IL-1␤, it significantly suppressed the inductive effect of IL-1␤.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies by our group and others have implicated several IL-1␤-induced genes in the progression of intervertebral disc degeneration, including matrix degrading enzymes, MMP-3, and ADAMTS-5, as well as PHD3 and syndecan 4 (3,34,35). Although CCN2 treatment alone had little effect on basal expression of these catabolic genes, when combined with IL-1␤, it significantly suppressed the inductive effect of IL-1␤.…”
Section: Discussionmentioning
confidence: 75%
“…5D). Our previous studies have shown that MEFs mimic many aspects of p65 transcriptional response in NP cells (29,31). We therefore used MEFs derived from p65…”
Section: -G)mentioning
confidence: 99%
“…Moreover, FIH-1 has also recently been reported to interact with and inhibit the proapoptotic protein Bax, independent of its hydroxylase activity (45). In light of our recent finding of PHD3 activating p65 signaling in NP cells independent of proline hydroxylation (46), it is important to also consider the potential role of FIH-1 independent of asparagine hydroxylation in NP physiology.…”
Section: Discussionmentioning
confidence: 99%